Observations and measurements of wing parameters of the selected beetle species and the design of a mechanism structure implementing a complex wing movement - Geisler, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
Beetle wings perform a flapping movement, consisting of the rotation relative to the two axes. This paper presents the results of observations and measurements of wings operating parameters in different planes of some beetle species. High speed photos and videos were used. The concept of the mechanism performing a complex wing movement was proposed and developed.
Keywords: biomimicry; wing; flapping mechanism; parameters